Sulforaphane is a reversible covalent inhibitor of 3‐chymotrypsin‐like protease of SARS‐CoV‐2. Issue 3 (5th March 2023) - Chen, Zinuo; Du, Ruikun; Cooper, Laura; Achi, Jazmin G.; Dong, Meiyue; Ran, Yan; Zhang, Jiwei; Zhan, Peng; Rong, Lijun; Cui, Qinghua
Abstract: The ongoing pandemic of coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has posed a major public health threat worldwide and emphasizes an urgent need for effective therapeutics. Recently, Ordonez et al. identified sulforaphane (SFN) as a novel coronavirus inhibitor both in vitro and in mice, but the mechanism of action remains elusive. In this study, we independently discovered SFN for its inhibitory effect against SARS‐CoV‐2 using a target‐based screening approach, identifying the viral 3‐chymotrypsin‐like protease (3CL pro ) as a target of SFN. Mechanistically, SFN inhibits 3CL pro in a reversible, mixed‐type manner. Moreover, enzymatic kinetics studies reveal that SFN is a slow‐binding inhibitor, following a two‐step interaction. Initially, an encounter complex forms by specific binding of SFN to the active pocket of 3CL pro ; subsequently, the isothiocyanate group of SFN as "warhead" reacts covalently to the catalytic cysteine in a slower velocity, stabilizing the SFN‐3CL pro complex. Our study has identified a new lead of the covalent 3CL pro inhibitors which has potential to be developed as a therapeutic agent to treat SARS‐CoV‐2 infection.